2002
DOI: 10.1021/jp013373a
|View full text |Cite
|
Sign up to set email alerts
|

Effective Medium Theory of Conduction in Stretched Polymer Electrolytes

Abstract: Recent experimental observations of anisotropic conductivity in stretched polymer electrolytes films of the polyethylene oxide family are discussed. The main experimental observations, enhancement of the ionic diffusion and conductivity in the stretch direction and decrease in these transport coefficients in the normal direction are interpreted in terms of an effective two-phase model. This two-phase model is based on the idea that a highly conducting phase is associated with oriented molecular structures whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…92 This model is based on the idea that a highly conducting phase is associated with oriented molecular structures which are surrounded by poorly conducting boundary regions. The model is evaluated within the framework of the differential effective medium theory (DEMT).…”
Section: 91mentioning
confidence: 99%
“…92 This model is based on the idea that a highly conducting phase is associated with oriented molecular structures which are surrounded by poorly conducting boundary regions. The model is evaluated within the framework of the differential effective medium theory (DEMT).…”
Section: 91mentioning
confidence: 99%
“…It was found that the more amorphous the PE, the less its lengthwise conductivity is influenced by stretching. A model that accounts for stretching-induced structural anisotropy accompanied by ion conduction enhancement was introduced in [9]. It addresses a transition from spherical to spheroidal shapes of the high conduction regions as a result of alignment.…”
Section: Introductionmentioning
confidence: 99%
“…12 is less impressive, with the correct trend seen only at low n values (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Given the simplified model used in the simulation, obtaining the correct trend as well as absolute ratio value over the entire n range (as in Fig.…”
Section: Temperature Effectmentioning
confidence: 94%
“…Therefore inter-chain transport is essential for long-range conduction. It has recently been found [5]- [8] that intra-chain transport is far more efficient than inter-chain hopping, making the latter process rate-limiting. The inter-chain ion hopping is assisted by a polymer segmental motion that controls the instantaneous distance between adjacent chains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation